Rating Accessibility of Packaging: A Medical Packaging Example. (3rd October 2013) - Rowson, Jen; Sangrar, Aamir; Rodriguez‐Falcon, Elena; Bell, Alison F.; Walton, Karen A.; Yoxall, Alaster; Kamat, Seri Rahayu
<x xml:space="preserve">Abstract</x> Few previous work has been undertaken in understanding issues surrounding dexterity and access to packaging. Researchers had access to users who had known dexterity issues and had been advised by their doctor to decant their medication into bottles rather than use unit‐dose blister packaging. Hence, it was decided to use a range of techniques to understand this problem. It was further proposed to develop a methodology by which the relative performance of packaging could be assessed with respect to dexterity issues. In this study, there were three objectives to carry out: motion‐capture analysis, grip analysis and dexterity analysis when opening the blister packs. Motion capture was carried out on eight people aged 55 years and older, a classification of the grips used when opening blister packs was performed on 57 people aged 18 years and older, and a Purdue Pegboard test was administered to 54 people aged 18 years and older. It was found out that there were four common types of grips used, out of which two of the grips were used by more than 88% of participants. With the motion capture, it was found that each grip and their various associated techniques were compared with each other. Grip 2 utilized the least finger movement. Using the dexterity test results, it was corroborated that dexterity decreases with age, and an accessibility score was developed that can be used by pack designers and manufacturers to assess pack performance. Future work is proposed to develop this methodology further. Copyright © 2013 John Wiley & Sons, Ltd.